MODEL PENINGKATAN KEPUASAN PELANGGAN TELKOMSEL (STUDI KASUS PADA KONSUMEN TELKOMSEL DI DKI JAKARTA) - Santoso, Danny; Mirza, Mirza (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
This study aims to analyze the effect of SERVQUAL and network quality in Telkomsel consumer satisfaction in DKI Jakarta, and as additionthis study also measuring gap analysis between the consumer expectation and Telkomsel’s performance.. Sampling method used was probability sampling by using cluster sampling system, this method is used because it’s considered the most suitable when the respondents is heterogent This research was conducted by questionnaire method, done to 385 customers of Telkomsel in DKI Jakarta. Quantitive analysis includes validity and reliability test, classical assumption test, coefficient of determination R2, F test, t-test and multiple regression analysis. R2 value of 0,59 indicates that 59,0% consumer satisfaction achieved was indeed influenced by independent variables (service quality and network quality) used in this study. Additionally, F 0,000 value suggested that service quality and network quality as independent variables simultaneously affect Telkomsel customer satisfaction.. service quality and network quality simultaneously are having significant influence to the Telkomsel customer satisfaction in Jakarta. Empathy and network quality dimension has the most significant in influencing Telkomsel customer satisfaction in Jakarta.